The genus Whiteringia: A review of its traditional uses, phytochemistry and pharmacology - Passos Pequeno, Andréia (2017)
The genus Witheringia belongs to Solanaceae family. Some of its species are widely used in traditional medicine to cure several disorders such as diabetes, cancer, malaria, helminthic infections, inflammatory disorders, digestive problems and others manifestations like fever, skin disease and general pain. The phytochemistry of this genus has been poorly studied, however some researchers reported the presence of some phytoconstituents which includes alkaloids, saponnins, tannins, flavonoids, anthraquinones and different types of withanolides such as physalins B, D and F. The physalins have attracted much attention in recent years due to their various biological activities. Despite the few studies, this plant has a promising pharmacological value for its various biological activities namely, anti-inflammatory, immunomodulatory, antimalarial and antidiabetic activities which are reported in the extracts of leaves and its phyto compounds of this plant. An overview of the current knowledge of the ethnopharmacology and phytochemical of the genus Witheringia and its physalins compounds is presented in this review.